2005
DOI: 10.1143/jjap.44.7482
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post Annealing on Performance of Polymer Light-Emitting Devices

Abstract: A high luminescence and a high efficiency could be obtained for polymer light emitting diodes (PLEDs) after post annealing at an appropriate temperature. Calcium was used as the cathode material of light emitting diodes based on 2,3-dibutoxy-1,4-poly(phenylene vinylene) (DB-PPV). Ca diffused into polymer and degraded the performance after PLEDs were post annealed at various temperatures except for 120°C. The luminescence of PLEDs reached 5343 cd/m2 after annealing at 120°C. The corresponding efficiency under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Poly( p -phenyene vinylene) (PPV) for application in optoelectronic fields had attracted great interest [ 1 ]. The polymer has certain advantages, such like low-cost, easy procession, and large-area display over light-emitting diodes (LEDs) made from inorganic material, especially in flexible displays [ 2 ]. Somehow, polymer LED (PLED) has one characteristic that its electron-injection is more difficult than its hole-injection due to the high energy barrier for electron-injection and low electron mobility in organic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Poly( p -phenyene vinylene) (PPV) for application in optoelectronic fields had attracted great interest [ 1 ]. The polymer has certain advantages, such like low-cost, easy procession, and large-area display over light-emitting diodes (LEDs) made from inorganic material, especially in flexible displays [ 2 ]. Somehow, polymer LED (PLED) has one characteristic that its electron-injection is more difficult than its hole-injection due to the high energy barrier for electron-injection and low electron mobility in organic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…21 Besides, the effects upon the performance of OLEDs by thermal treatment have been investigated. Tu et al 22,23 and Ahn et al 24 have reported the effect of postannealing on the performance of polymer LEDs and blendedlayer OLEDs, respectively. Chen et al 25 reported in situ postgrowth annealing of the organic layer before metal cathode was conducted on tris-͑8-hydroxyqunoline͒ aluminum ͑Alq 3 ͒ to improve the performance of Alq 3 -based OLEDs.…”
mentioning
confidence: 99%
“…3) The luminous efficiency of PLEDs based with 2,3dibutoxy-1,4-poly(phenylene vinylene) (DBPPV) emissive layer was improved by post-annealing effect. 4) In this paper, we report the post-annealing effect on the electroluminescence of DBPPV-based PLEDs.…”
Section: Introductionmentioning
confidence: 98%